The value of enzymes added to cattle rations - Richardson, D.; Smith, E.F.; Koch, B.A.; Tsien, W.S.; Boren, Fred W. (Kansas Agricultural Experiment Station, 2011)
Three lots of 10 animals were fed the same ration except for the added enzymes. The average daily ration is shown in Table 25, as are results of the test for the first 112 days. There are no significant differences in gains at present; however, lot 12, which receives a combination of enzymes that act upon carbohydrates and protein, has a slightly higher rate of gain. Animals in lot 12 also have a tendency to clean up their feed better than those in either other lot. This test will be continued until the animals are ready for slaughter.
Keywords: Cattle; Dried corn; Enzymes; Gain